Доісторична пастуша будівля-“стая” з Добростан - Павлів, Д.; Петегирич, В. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
The article is dedicated to researches of large building dated back to Early Iron Age, which was discovered during the excavations, carried out near Dobrostany village (Javoriv district, L’viv region). Remains of this construction preserved as ditches and post-pits deepened into mainland and filled by humus soil. Building was rectangular in plan and it’s dimensions were 11,4×6,5 meters. It was oriented by the line East-West by its longest side. Large wooden posts situated on corners by perimeter of the building along walls and on the center of the building were the base of this construction. Roof with two slopes were lean on them. Walls were made of wooden blocks situated horizontally. Building consists of three cameras. Entrance (oriented to South) was in largest central camera, were fireplace was placed. Fragments of ceramic ware found in remains of dwelling, fireplace and cultural layer dated back this construction to VII – V centuries. Such ceramic was discovered on monuments of Cherepyno-Lahodivs’ka group and Luzhyts’ka (Tarnobzhets’ka) culture. Arcaeological and ethnographical materials allow us to interpret this construction like short-time herders’ “staia” on the place of pasture of cattle.